The PALEA struggle against outsourcing and contractualization in the airline industry in the Philippines - Ramon A. Certeza (International Labour Organization (ILO), 2018)
The paper tells the story of the drawn-out struggle of the Philippine Airlines Employees Association (PALEA) to reverse the trend of outsourcing in the Philippine Airlines (PAL). It highlights the fight-back strategies adopted by PALEA in its attempt to stop the contractualization of labour in the airline industry. Through a combination of traditional and innovative strategies, including a wellplanned and coordinated national campaign that involved different sectors of Philippines society, trade unions from other countries, and international trade union support organizations, PALEA was able to achieve initial victories. Nonetheless, the company continues its practice of outsourcing with detrimental effects on workers' job security. The PALEA struggle provides inspiration and valuable lessons that, despite an uphill battle against a giant airline company, workers' determination to fight for their rights can provide a strong resistance against corporate power.
Keywords: 330